2022
DOI: 10.3390/ijerph19042368
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Excess, All-Cause Mortality among Black, Hispanic, and White Veterans at the U.S. Department of Veterans Affairs during the COVID-19 Pandemic

Abstract: Background: From 2019 to 2020, all-cause mortality in the U.S. increased, with most of the rise attributed to COVID-19. No studies have examined the racial disparities in all-cause mortality among U.S. veterans receiving medical care (VA users) at the U.S. Department of Veterans Affairs (VA) during the pandemic. Methods: In the present paper, we conduct a longitudinal study examining the differences in mortality among White, Black, and Hispanic veterans, aged 45 years and older, during the first, full year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Due to the unique demographic characteristics of this population, questions have been raised about the relevance of studies in this population. Previous reports show that death rates among those who typically received care in the VA health system were less affected than death rates among the general US population during the COVID-19 pandemic, despite higher rates of comorbidities in the veteran population . However, veterans enrolled in VA health care also differ from the general US population in age, sex, racial and ethnic composition, and geographic distribution, and each of these factors has been associated with mortality rates in general and death rates due to COVID-19 specifically .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique demographic characteristics of this population, questions have been raised about the relevance of studies in this population. Previous reports show that death rates among those who typically received care in the VA health system were less affected than death rates among the general US population during the COVID-19 pandemic, despite higher rates of comorbidities in the veteran population . However, veterans enrolled in VA health care also differ from the general US population in age, sex, racial and ethnic composition, and geographic distribution, and each of these factors has been associated with mortality rates in general and death rates due to COVID-19 specifically .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the existing work found that excess mortality was highest for Hispanic Veterans (34%), followed by Black Veterans (32%). 18 Our estimates suggest that excess mortality was highest for Native American Veterans (40%) followed by Black (32%) and Hispanic Veterans (26%), respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Prior work found a 16.7% overall rate of excess mortality for all Veterans, and minoritized Veterans experienced higher rates of excess mortality compared to White Veterans in simple comparisons. 18 , 19 This existing work, however, was limited in scope by focusing on a narrow cohort of Veterans over a short period of time, with no ability to account for comorbidities that may increase the risk of death during the COVID‐19 pandemic. We extend these existing works and leverage a rigorous, previously‐validated approach to identify excess mortality attributable to COVID‐19 stratified by race and ethnicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports show that death rates among those who typically received care in the VA system were less affected than the general US population during the COVID-19 pandemic, despite higher rates of comorbidities [5][6][7]. However, Veterans enrolled in VA care also differ from the general US population in age, sex, racial/ethnic composition, and geographic distribution, and each of these factors has been associated with mortality rates in general and deaths rates due to COVID-19 specifically [8][9][10].…”
Section: Introductionmentioning
confidence: 99%